Attenuated CSF‐1R signalling drives cerebrovascular pathology. Issue 2 (22nd December 2020) - Delaney, Conor; Farrell, Michael; Doherty, Colin P; Brennan, Kiva; O'Keeffe, Eoin; Greene, Chris; Byrne, Kieva; Kelly, Eoin; Birmingham, Niamh; Hickey, Paula; Cronin, Simon; Savvides, Savvas N; et al.
Abstract: Cerebrovascular pathologies occur in up to 80% of cases of Alzheimer's disease; however, the underlying mechanisms that lead to perivascular pathology and accompanying blood–brain barrier (BBB) disruption are still not fully understood. We have identified previously unreported mutations in colony stimulating factor‐1 receptor ( CSF‐1R ) in an ultra‐rare autosomal dominant condition termed adult‐onset leucoencephalopathy with axonal spheroids and pigmented glia (ALSP). Cerebrovascular pathologies such as cerebral amyloid angiopathy (CAA) and perivascular p‐Tau were some of the primary neuropathological features of this condition. We have identified two families with different dominant acting alleles with variants located in the kinase region of the CSF‐1R gene, which confer a lack of kinase activity and signalling. The protein product of this gene acts as the receptor for 2 cognate ligands, namely colony stimulating factor‐1 (CSF‐1) and interleukin‐34 (IL‐34). Here, we show that depletion in CSF‐1R signalling induces BBB disruption and decreases the phagocytic capacity of peripheral macrophages but not microglia. CSF‐1R signalling appears to be critical for macrophage and microglial activation, and macrophage localisation to amyloid appears reduced following the induction of Csf‐1r heterozygosity in macrophages. Finally, we show that endothelial/microglial crosstalk and concomitant attenuation of CSF‐1R signalling causes re‐modelling of BBB‐associated tight junctions and suggest that regulating BBB integrity and systemic macrophage recruitment to the brain may be therapeutically relevant in ALSP and other Alzheimer's‐like dementias. Synopsis: Two familial cohorts of ALSP, with novel pathological CSF1R variants were examined and an associating cerebrovascular amyloid‐β pathology identified. Deficits in peripheral macrophage function and blood‐brain barrier maintenance identified and suggested to contribute to ALSP. Two novel pathological CSF1R mutations were identified and characterised, indicating the observed pathology to be driven by CSF1R haploinsufficiency. Cerebral amyloid angiopathy (CAA) was identified as a novel accompanying pathology in ALSP, providing a potential single‐gene mutation capable of driving CAA itself. CSF1R heterozygosity was shown to negatively impact macrophage differentiation, phagocytosis and chemotaxis to the brain in response to amyloid‐β. Microglia heterozygous for Csf1r were shown to be uniquely capable of downregulating tight junction expression in brain endothelial cells. Abstract : Two familial cohorts of ALSP, with novel pathological CSF1R variants were examined and an associating cerebrovascular amyloid‐β pathology identified. Deficits in peripheral macrophage function and blood‐brain barrier maintenance identified and suggested to contribute to ALSP.